Transcriptomic Profiles of Senegalese Sole Infected With Nervous Necrosis Virus Reassortants Presenting Different Degree of Virulence - Labella, Alejandro M.; Garcia-Rosado, Esther; Bandín, Isabel; Dopazo, Carlos P.; Castro, Dolores; Alonso, M. Carmen; Borrego, Juan J. (Frontiers in Immunology, 2018)
Betanodaviruses (NNV) are the causative agent of the viral encephalopathy and retinopathy (VER), a disease that affects cultured Senegalese sole (Solea senegalensis). NNV reassortants, combining genomic segments from RGNNV and SJNNV genotypes, have been previously isolated from several fish species. The wild-type reassortant wSs160.03, isolated from Senegalese sole, has been proven to be more virulent to sole than the parental genotypes (RGNNV and SJNNV), causing 100% mortality. Mutations at amino acids 247 (serine to alanine) and 270 (serine to asparagine) in the wSs160.03 capsid protein have allowed us to obtain a mutant reassortant (rSs160.03247+270), which provokes a 40% mortality decrease. In this study, the RNA-Seq technology has been used to comparatively analyze Senegalese sole transcriptomes in two organs (head-kidney and eye/brain) after infection with wild-type and mutant strains. A total of 633 genes were differentially expressed (DEGs) in animals infected with the wild-type isolate, (with higher virulence), whereas 393 genes were differentially expressed in animals infected with the mutant strain (37.9% decrease in the number of DEGs). To study the biological functions of detected DEGs involved in NNV infection, a gene ontology (GO) enrichment analysis was performed. Different GO profiles were obtained in the following subclasses: (i) biological process; (ii) cellular component; and (iii) molecular function, for each viral strain tested. Immune response and proteolysis have been the predominant biological process after the infection with the wild-type isolate, whereas the infection with the mutant strain induces proteolysis in head-kidney and inhibition of vasculogenesis in nervous tissue. Regarding the immune response, genes coding for proteins acting as mediators of type I IFN expression (DHX58, IRF3, IRF7) and IFN-stimulated genes (ISG15, Mx, PKR, Gig1, ISG12, IFI44, IFIT-1, to name a few) were up-regulated in animals infected with the wild-type isolate, whereas no-differential expression of these genes was observed in samples inoculated with the mutant strain. The different transcriptomic profiles obtained could help to better understand the NNV pathogenesis in Senegalese sole, setting up the importance as virulence determinants of amino acids at positions 247 and 270 within the RNA2 segment.